2015
DOI: 10.1177/0883073815601499
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding and Managing Autism Spectrum Disorders

Abstract: Autism spectrum disorder in children is a group of neurodevelopmental disorders characterized by difficulties with social communication and behavior. Growing scientific evidence in addition to clinical practice has led the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) to categorize several disorders into the broader category of autism spectrum disorder. As more is learned about how autism spectrum disorder manifests, progress has been made toward better clinical management including earlier dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…La elevada prevalencia obtenida en el trabajo, si bien es similar a la reportada por el Center for Disease Control (CDC) de Estados Unidos, puede deberse a la edad de los niños, ya que a menor edad los síntomas no persisten en todos, sino sólo en un 85 a 90% de ellos; a diferencia de lo que ocurre con el diagnóstico de TEA a mayor edad que es más estable. Por otra parte, no se registraron datos de factores ambientales, los cuales aumentan la prevalencia de TEA y podrían explicar la cifra obtenida, tales como: edad de ambos padres, patología del embarazo, prematurez, entre otros 14,15 .…”
Section: Discussionunclassified
“…La elevada prevalencia obtenida en el trabajo, si bien es similar a la reportada por el Center for Disease Control (CDC) de Estados Unidos, puede deberse a la edad de los niños, ya que a menor edad los síntomas no persisten en todos, sino sólo en un 85 a 90% de ellos; a diferencia de lo que ocurre con el diagnóstico de TEA a mayor edad que es más estable. Por otra parte, no se registraron datos de factores ambientales, los cuales aumentan la prevalencia de TEA y podrían explicar la cifra obtenida, tales como: edad de ambos padres, patología del embarazo, prematurez, entre otros 14,15 .…”
Section: Discussionunclassified
“…However, early diagnosis of autism remains rare, especially in certain disadvantaged communities [16]. This is exacerbated by the fact that indications of most spectrum diagnoses and the essential symptoms are unfortunately only noticed around the age of six years and older [17]. A study [18] by McKenzie et al (2015) found that prior to diagnosis, many families may suspect something is not right with their child, but they do not report their suspicions due to a lack of knowledge and understanding of normal developmental patterns, as well as of autism and its symptoms [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to problems in social skills, communication, and language skills, children with ASD have restricted interests and repetitive behaviors. In addition, among children with ASD, motor impairments are among the earliest emerging correlated difficulties (Arabameri & Sotoodeh, 2015;Germain, Eppinger, Mostofsky, DiCicco-Bloom, & Maria, 2015), even though they are not considered diagnostic symptoms (Liu, Hamilton, Davis, & ElGarhy, 2014). Previous studies of individuals with ASD have documented delayed motor milestones and fundamental motor skills (Arabameri & Sotoodeh, 2015;Staples & Reid, 2010), deficits in postural stability and motor coordination (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010;Nobile et al, 2011), impairment in catching objects accurately (Sacrey, Germani, Bryson, & Zwaigenbaum, 2014;Wang et al, 2014;Whyatt & Craig, 2013), gait abnormalities, problems in joint flexibility and movement speed (Jansiewicz et al, 2006), and deficits in balance (Freitag, Kleser, Schneider, & von Gontard, 2007;Nobile et al, 2011), all of which are a further basis for other minor and major motor behavior problems.…”
Section: Introductionmentioning
confidence: 99%